STRATEGI PENGEMBANGAN PRODUK BANK SYARIAH DI INDONESIA - gemina, dwi (Universitas Djuanda Bogor, 2011)
Islamic Banks and Sharia Rural Banks are expected to be a means by which to collect funds from the majority Muslim community, once channeled into the community with products that are attractive and accessible to the public. Islamic Banking Products is a market segment that is relatively certain that the Islamic community but it is also possible exploited by non-Muslim community. Therefore, it is how the efforts made so it appears as a product that mkenarik and to create satisfaction for consumers. From the point of satisfaction not only the satisfaction of birth but also the inner satisfaction, which should be perhatihan is a product that does not contain elements Islam. Kehadiran prohibition in Islamic banks in Indonesia requires the participation of the Islamic community who think that conventional banking practices do not fit on the sharia. Operasinal Islamic banks showed the development of more advanced compared to the BPRS. BPRS still largely experiencing difficulty in obtaining margin is the level of revenue sharing.